2013
DOI: 10.1186/1472-6920-13-30
|View full text |Cite
|
Sign up to set email alerts
|

Computer game-based and traditional learning method: a comparison regarding students’ knowledge retention

Abstract: BackgroundEducational computer games are examples of computer-assisted learning objects, representing an educational strategy of growing interest. Given the changes in the digital world over the last decades, students of the current generation expect technology to be used in advancing their learning requiring a need to change traditional passive learning methodologies to an active multisensory experimental learning methodology. The objective of this study was to compare a computer game-based learning method wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
91
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(102 citation statements)
references
References 49 publications
5
91
0
6
Order By: Relevance
“…Nevertheless, educational computer games can provide more interesting environments for knowledge than traditional methods [23][24][25][26][27][28][29][30][31][32][33], speaking to our students in a language they are used to. However, the objective must not be limited to the packaging, as the value of well-designed and well-implemented tools depends on how they are integrated into the course [13].…”
Section: Educational Games and Traditional Teachingmentioning
confidence: 99%
“…Nevertheless, educational computer games can provide more interesting environments for knowledge than traditional methods [23][24][25][26][27][28][29][30][31][32][33], speaking to our students in a language they are used to. However, the objective must not be limited to the packaging, as the value of well-designed and well-implemented tools depends on how they are integrated into the course [13].…”
Section: Educational Games and Traditional Teachingmentioning
confidence: 99%
“…Teachers are currently working hard to educate a new generation of engineering students using old methods, incorporating tools that are no longer effective and providing knowledge (information, concepts, relationships, and so on) using only speech without interaction among students [51,18]. According to , students belonging to the new generation of engineers demand the use of technology in advancing their learning by changing traditional passive learning methodologies to active multisensory experimental learning methodologies. In this context, some studies have reported the effectiveness of educational computer games in enhancing the engineering student's learning interest and motivation within contexts where learning methods were once traditional.…”
Section: Introductionmentioning
confidence: 99%
“…According to [42], students belonging to the new generation of engineers demand the use of technology in advancing their learning by changing traditional passive learning methodologies to active multisensory experimental learning methodologies. In this context, some studies have reported the effectiveness of educational computer games in enhancing the engineering student's learning interest and motivation within contexts where learning methods were once traditional.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, it is unclear whethertheimprovedinterestandsatisfactionseenwithelectronic educational content translates to improved learning and material retention.Thereislimiteddatacomparinggame-basedteachingto didactic lectures withrespect to information retention andconcept understanding, and the few studies performed have shown conflicting results [15,16]. Assessing the value of a game-based format has not been previously attempted in the setting of medical student education in radiology.…”
Section: Introductionmentioning
confidence: 99%